Why should I use a multi-hazard app? Assessing the public's information needs and app feature preferences in a participatory process. (15th April 2021) - Dallo, Irina; Marti, Michèle
Abstract: In the age of nearly instant information and high-bandwidth communication, public expectations regarding the availability of authoritative short-term and real-time hazard information are evolving rapidly. Despite the existence of numerous apps covering hazard information, little research has been conducted to assess what the public actually expects from such an app. Perceived usefulness is crucial as the public will only use apps offering an added value to them. Several studies have identified that people prefer an app combining relevant hazards instead of single hazard apps. Therefore, we focused our analysis on multi-hazard apps. With seven virtual interactive workshops, we assessed the public's information needs and app feature preferences. With respect to the content of multi-hazard apps, our results show that participants would mainly combine natural hazards but also have an interest in integrating anthropogenic and socio-natural hazards. To this end, participants advocate sending push notifications for low-probability hazards via general-purpose apps (e.g., weather apps) to reach a larger audience. Despite the desired diversity of hazard information, participants wish for an app focusing on relevant information only and redirecting users to other authorized sources for further information. Participants define the following as relevant information: location, time, hazard severity, behavioral recommendations and the contact details of emergency services. In addition, they wish for the following features: push notifications, a help button, a sharing function, a chat forum, an "I am safe" button, and a "Report an event" button. Highlights: Three reasons why one should use a multi-hazard app: First, the public demands for it. Second, the responsible authorities can together reach a larger audience. Third, interactive features can increase users' ability to manage different hazards.